The role of gut microbiota dysbiosis in the inflammatory pathogenesis of diabetic retinopathy - Xie, Liqing; Lin, Wenjian (Frontiers in Immunology, 2025)
Diabetic retinopathy, a prevalent microvascular complication of diabetes mellitus, is characterized by its increasing global prevalence and stands as the leading cause of visual impairment and blindness in adults. The pathogenesis of diabetic retinopathy involves multifactorial interactions, among which inflammatory responses play a pivotal role in disease progression. With the emergence of the “gut-retinal axis” concept, growing evidence has elucidated the intricate association between gut microbiota dysbiosis and the development of diabetic retinopathy. Studies have revealed significant differences in gut microbiota composition and diversity between patients with diabetic retinopathy and those without diabetic retinopathy. Dysbiosis of the gut microbiota compromises intestinal barrier integrity, thereby facilitating the translocation of intestinal metabolites into systemic circulation. This process may trigger the activation of systemic inflammatory responses, thus contributing to the pathogenesis and progression of diabetic retinopathy. This review examines the metabolic disturbances and systemic inflammatory responses induced by gut microbiota dysbiosis in diabetes, providing an in-depth analysis of how gut microbiota dysbiosis influences the inflammatory mechanisms underlying diabetic retinopathy. Furthermore, it summarizes the protective effects of anti-diabetic drugs on diabetic retinopathy by modulating the intestinal microenvironment, offering novel perspectives for the treatment of diabetic retinopathy.